(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article discusses the issues of increasing farmers’ incomes through the introduction of insurance with the intensive development of agriculture on a scientific basis, based on the priorities of the development strategy of New Uzbekistan. Furthermore, recommendations of increasing the farmer`s income in the agro-industrial complex and their insurance protection are given.